Being Sceptical about Kripkean A Posteriori Necessities and Natural Kinds - Sepetyi, D.; Сепетий, Дмитро Петрович (My University, 2020)
One of the most celebrated discoveries in the analytic philosophy of the second half of XX century is that of the existence of necessary a posteriori truths, made by Saul Kripke. As Hilary Putnam (the second most influential defender and developer of the theory of necessary a posteriori truths) puts it, “[s]ince Kant there has been a big split between philosophers who thought that all necessary truths were analytic and philosophers who thought that some necessary truths were synthetic a priori. But none of these philosophers thought that a (metaphysically) necessary truth could fail to be a priori” [Putnam, 1975: p. 151].
https://orcid.org/0000-0003-2110-3044
Keywords: a posteriori necessary truth; necessity; contingency; metaphysical possibility; natural kind